Adoption of Alternative Building Materials in Construction of Residential Property in Kenya - Gekonge, Samuel Nyakundi (2021)
Housing can be looked at as the provision of shelter and a place to live in. It is therefore necessary to have adequate shelter that is affordable and decent. Adequate shelter in this context refers to good quality rental and owner occupier housing units that can be affordable to the low-income families that are the main focus of this study. The main objective of this study is to examine the determinants of affordable housing in Nairobi, Kenya. In this study, the population consisted of a total of 50 respondents who comprised of individuals who have already purchased an affordable house as well as those who wish to purchase an affordable house. Data collection was by means of a questionnaire, as well as interviews that were conducted. Primary data was used and coded and finally analysed using the descriptive statistics to describe each variable under study. Coefficient of variation was also used to analyse the variation of the data. The Microsoft Excel software used to present the data in tables. The findings established that financial institutions prefer to give loans to individuals who are formally employed; however, majority of the population are in the informal employment. The results also established that a factor affecting affordability of housing in regard to interest rates was that majority of the borrowers would prefer to get a loan when the interest rates are low and stable, then it becomes much cheaper to purchase or build an affordable home. The main conclusion provided that financial institutions had more preference on individuals who are formally employed as opposed to those who do not seem to earn a steady income. It was also noted that the tax incentives provided by the government would be more useful to developers who come up with huge affordable housing projects. Page 5 of 69 Samuel Nyakundi Gekonge I18015913@student.newinti.edu.my The study recommended that the tax incentives that have been provided for by the government be easily understood by all stakeholders, the tax benefits should also benefit both the large and small size developers. It was also recommended that the financial institutions come up with systems that can be able to cater for those borrowers who are not in the formal employment. Lastly it was recommended that more research should be carried out on cheaper building materials that are effective and can be used to build houses; this would result in the eventual costs of building a house to reduce significantly. The study also suggests that future research could be done on the use of cheaper building materials on low-cost housing projects in Nairobi, Kenya. Low- cost housing is an area of interest in developing countries including Kenya.